Efesiensi Teknis Usaha Tani Kentang di Kabupaten Lumajang - Shohibul Ulum (UNEJ e-Proceeding, 2018)
Potatoes has important role in food security. It can substitute main food crop as rice.Lumajang Regency is one of main potato producers in East Java, Indonesia. Therefore, potato isexpected to make high contribution toward regional GDP. However, the annual productivity ofpotato in Lumajang has been below national level. There was a productivity gap as well as 3-5tones per hectares towards national level in the last years. This study was aimed to determine: 1)technical efficiency achievement among potato farmers, 2) technical efficiency determinant inpotato farming. This study was conducted in Argosari village, Senduro District, LumajangRegency. Sixty farmers was randomly selected and structurally interviewed by questionnaire.Stochastic frontier analysis was employed to determine the objective. The result showed that: 1) theaverage technical efficiency which was achieved by sampling farmers is 0.59 or 59%. It means thatpotato farmers can produce 59% from their maximum production. For about 67% of samplingfarmers ran their potato farming under inefficient condition. 2) There are two factors which havesignificant effect toward technical efficiency: household size and crop system. Household hasopposite effect toward technical efficiency. Mixed cropping system is more efficient than solecropping one.